2018
DOI: 10.3201/eid2409.180343
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence ofBorrelia burgdorferisensu stricto–Infected Blacklegged Ticks in Tennessee Valley, Tennessee, USA

Abstract: In 2017, we surveyed forests in the upper Tennessee Valley, Tennessee, USA. We found Ixodes scapularis ticks established in 23 of 26 counties, 4 of which had Borrelia burgdorferi sensu stricto–infected ticks. Public health officials should be vigilant for increasing Lyme disease incidence in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…However, the situation is complicated by the history of I. scapularis in North America, which has been characterized by range expansions from refugia in the northeastern coastal states and northern midwestern sites [41]. Indeed, recent studies have identified expansion of northern-type ticks south along the Appalachian Mountains of southwestern Virginia [42] and possibly in river valleys in northeastern Tennessee [43]. These ticks might act like northern ticks, resulting in an initial increase in the incidence of Lyme disease in the south.…”
Section: Plos Biologymentioning
confidence: 99%
“…However, the situation is complicated by the history of I. scapularis in North America, which has been characterized by range expansions from refugia in the northeastern coastal states and northern midwestern sites [41]. Indeed, recent studies have identified expansion of northern-type ticks south along the Appalachian Mountains of southwestern Virginia [42] and possibly in river valleys in northeastern Tennessee [43]. These ticks might act like northern ticks, resulting in an initial increase in the incidence of Lyme disease in the south.…”
Section: Plos Biologymentioning
confidence: 99%
“…The cause of this disparity is not entirely understood; however, it is suspected that differences in host ecology and/or tick questing or feeding behavior may play a role 27,28 . Recently, however, there have been increased/first detections of B. burgdorferi -infected I. scapularis in some southeastern states (i.e., Kentucky and Tennessee) so continued surveillance is warranted 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of canine serologic data confirmed increasing trends in seroprevalence of Bb and Anaplasma spp. in several areas, including northern New England, upstate New York, and western Pennsylvania, as well as in some southern states where the I. scapularis-pathogen-reservoir host maintenance cycles necessary to maintain these agents have apparently only recently become established [26,27]. Interestingly, the data in the present study also documented for the first time decreasing trends in canine seroprevalence for these tick-borne agents in some regions, including in several Mid-Atlantic States and in the Midwest where autochthonous transmission of Bb and Ap has long been recognized.…”
Section: Discussionmentioning
confidence: 99%